IMPACT OF TOURISM ON SOCIAL ECONOMY OF THE COMMUNITY (Study in the Lappa Laona High Land Tourism Area, Tanete Riaja District, Barru Regency) - Masyitah (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal